Noncompaction and Dilated Cardiomyopathy in a Patient with Schizophrenia. (31st July 2016) - Finsterer, Josef; Stöllberger, Claudia
Abstract : Objectives. Psychosis and left ventricular hypertrabeculation (or noncompaction) (LVHT) have not been described in the same patient. Here we report a patient with a long-term history of schizophrenia who was later diagnosed with dilated cardiomyopathy (dCMP) and LVHT. Case Report. A 47-year-old Caucasian male developed nondifferentiated schizophrenia at the age of 26 y. Since the age of 33 y he was regularly drinking alcohol. At the age of 47 y he developed heart failure. Transthoracic echocardiography showed an enlarged left ventricle, reduced systolic function, and surprisingly LVHT in the apical segment. Additionally, the left atrium was enlarged, the right ventricular cavities were mildly enlarged, and there were pulmonary hypertension and a small pericardial effusion. Cardiac MRI confirmed the echocardiographic findings. Since coronary angiography was normal, dilated cardiomyopathy was additionally diagnosed. Since he was taking clozapine during years, dilated cardiomyopathy could be due to not only alcohol consumption but also the long-term neuroleptic medication. Conclusions. LVHT may be associated with nondifferentiated psychosis. Management of LVHT is challenging in patients with psychosis due to poor compliance and adherence of these patients. Patients with LVHT and psychosis need particular attention since they usually take cardiotoxic drugs for a long time, which may further deteriorate the prognosis of LVHT.